The association of sexual trauma with persistent pain in a sample of women veterans receiving primary care. - Haskell, Sally G; Papas, Rebecca K; Heapy, Alicia; Reid, M C; Kerns, Robert D (Pain medicine (Malden, Mass.), 2008)
Women veterans report high rates of persistent pain and high rates of sexual trauma. We sought to determine whether the presence and intensity of persistent pain, as well as level of pain-related interference, in the VA Connecticut Women's Clinic population was positively associated with reports of sexual trauma.
Keywords: Adult; Aged; Association; Chronic Disease; Female; Humans; Middle Aged; Military Personnel; Pain; Pain Measurement; Primary Health Care; Sex Factors; Sex Offenses; Sexual Harassment; United States; Veterans; Women's Health